One Year of #GamerGate: The Shared Twitter Link as Emblem of Masculinist Gamer Identity. Issue 8 (25th July 2019) - Dowling, David O.; Goetz, Christopher; Lathrop, Daniel
Since the #GamerGate controversy erupted in 2014, anti-feminist gamers continue to lash out at feminists and supporters of progressive and inclusive gaming content. A key strategy in this discourse is the sharing of content via links on Twitter, which accompany messages positioning the sender on either side of the debate. Through qualitative analysis of a data set drawn from 1, 311 tweets from 2016 to 2017, we argue that tweeted links are a salient tool for signaling affiliation with gaming communities. For anti-feminist gamers, the tweeted link defines masculinist gamer identity and constructs social boundaries against the increasing diversification of video game culture reflected in higher overall rates of feminist tweets. Links can be construed as revelatory of boundary work and thus can help shed insight on the extent to which #GamerGate discourse was intended to defend gaming culture as an exclusively masculine space.